EVALUASI MUTU STRUKTUR ATAS GEDUNG KRIS RSUD KEDIRI - Shofiyah, Qurrotus; Ayu Kumala, Erfinda; Tri Budiatma, Angga (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2025)
The Construction Project of the KRIS Building at RSUD Kediri Regency serves as a crucial effort in the development of healthcare facilities in the region. It is located at Jl. Pahlawan Kusuma Bangsa No.1, Palem Village, Pare District. The quality of the superstructure in a construc- tion project is significantly influenced by its compliance with the technical specifications that have been established. This study aims to evaluate the conformity of the superstructure work quality in the construction of the KRIS Building at RSUD Kediri Regency with technical specifications, in- cluding the Work Plan and Requirements (RKS), construction drawings, and the Indonesian Na- tional Standard (SNI). The research employs methods such as comparison through a conformity checklist form, analysis of laboratory test results for concrete and steel materials, and distribution of questionnaires to contractors and project supervisors. The assessed factors include materials, imple- mentation methods, labor, supervision, and the equipment used in the project. Based on the research findings on the superstructure work of the KRIS Building construction project at RSUD Kediri Re- gency, the conformity with technical specifications in the reinforcement inspection items (X.1–X.7) and casting items (Y.1–Y.8) recorded 100% compliance in Column Zone 1, 99% in Column Zone 2, 98% in beams and slabs of Zone 1, and 95% in Zone 2. The questionnaire results revealed that 20 key variable factors affecting the quality compliance in the construction of the KRIS Building con- tributed to 78,27% of the total influence on quality.